ANALISIS KELAYAKAN FINANSIAL PADA INDUSTRI JAGAD SUTERA DI KELURAHAN KAMONJI KECAMATAN PALU BARAT KOTA PALU - Nurmala Ilyas; Saharia Kassa; Abdul Muis (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research was aimed to analyze the financial feasibility at Jagad Sutera Industry. It was conducted in Kamonji, West Palu in April to June 2014. The respondents were purposively determined.  The respondents chosen from within the industry were 1 leader and 3 workers. Data was analyzed using financial worthiness analysis employing 4 indicators: Net present value (NPV), net benefit cost ratio (Net B/C), internal rate of return (IRR), and payback Period (PP).  The results of this research indicated that the NPV during the period of 2011 to 2014 was IDR 19,382,741; the net B/C was 1.65; the IRR was 16 %, and the PP had a payback period of 2 years 9months. It indicates that Jagad Sutera Industry is financiallyfeasible to operate.Key words: Financial Feasibility, Jagad Sutera, Silk Warm.